Pengaruh Literasi Keuangan, Pengetahuan Investasi, dan Kemajuan Teknologi Terhadap Minat Investasi Mahasiswa pada Pasar Modal - Auwidad, Riskiya; Sujatmika, Sujatmika (Innovative: Journal Of Social Science Research, 2025)
The purpose of this study is to determine how financial literacy, investment knowledge, and new technological developments impact students' investment interest in the capital market. This study is a quantitative type that uses hypothesis testing and multiple linear regression analysis.The population of this study were students from the Accounting Department, Faculty of Economics & Business, UPN “Veteran” Yogyakarta Class of 2021, 2022 and 2023. The sampling technique used was random sampling, with a sample size of 110 students. The primary data for this study were respondents' answers to the questionnaire, which were processed using the SPSS version 25 program. The results based on the t-test (partial) showed that knowledge about investment and finance influenced students' investment interest. While technological advances did not affect students' desire to invest.